TOWARD A FULLY AND ABSOLUTELY RASTER-BASED EROSION MODELING BY USING RS AND GIS - Bambang Sulistyo; Totok Gunawan; Hartono .; Projo Danoedoro (Faculty of Geography, Universitas Gadjah Mada, 2009)
The erosion map data is one of important data used in planningconservation of degraded land. Generally, erosion data is predicted using a modelbecause to gain actual erosion requires much resource (timely, costly and labourintensive). USLE (Universal Soil Loss Equation) is one of existing erosion modelsapplied worlwide, including Indonesia. Nevertheless, erosion analysis conducted isbased on analysis using vector-based maps. This method involves simplification,either algorithms or procedures, and subject to subjectivity, so the result has highuncertainty. This article deals with the idea to build a fully raster-based erosionmodeling. Steps required to obtain raster-based data was highlighted as from thebeginning up to the model validation to get an absolute model. The integration ofremote sensing and GIS was inevitably usedfor the analysis.